(untitled) (Journal of Hama University, 2021)
This study examines and measures competition between conventional private banks operating in Syria and its impact on their risks namely: credit and insolvency risks. Using semi-annual bank-level data of 10 private commercial banks through the period 2008-2018, panel data analysis is employed to achieve the study objectives. Our main findings suggest that the degree of competition among banks, measured using Lerner index for market power, is low and far from perfect competition. Moreover, our empirical findings support the competition-fragility paradigm. Increased competition among banks tends to increase their incentive for risk-taking to maximize their profits, which leads to higher credit and insolvency risks.